An alveolar recruitment maneuver followed by positive end-expiratory pressure improves lung function in healthy dogs undergoing laparoscopy. (September 2018) - Di Bella, Caterina; Lacitignola, Luca; Grasso, Salvatore; Centonze, Paola; Greco, Antonella; Ostuni, Rossella; Crovace, Antonio; Staffieri, Francesco
Abstract: Objective: To evaluate the effects of an alveolar recruitment maneuver (ARM) followed by 5 cmH2 O positive end-expiratory pressure (PEEP) in dogs undergoing laparoscopy. Study design: Prospective, randomized clinical study. Animals: A group of 20 dogs undergoing laparoscopic ovariectomy. Methods: Dogs were sedated with acepromazine and methadone intramuscularly; anesthesia was induced with propofol intravenously and maintained with inhaled isoflurane. The following baseline ventilatory setting (BVS) was administered: tidal volume of 12 mL kg –1, inspiratory to expiratory ratio of 1:2, inspiratory pause 25% of inspiratory time, no PEEP and a respiratory rate to maintain end-tidal carbon dioxide tension between 5.3 and 7.3 kPa. Then, 10 minutes after the pneumoperitoneum, 10 dogs (RM) underwent a sustained inflation ARM followed by BVS plus 5 cmH2 O PEEP, while 10 dogs (NO-RM) were left with BVS throughout the procedure. Gas exchange and respiratory system mechanics were evaluated before the pneumoperitoneum (PPpre), before ARM (PP10), 30 minutes later (PP30) and 20 minutes after pneumoperitoneum discontinuation (PPpost20). Data were analyzed usinganova ( p  < 0.05). Results: The Fshunt at PP30 and PPpost20 was lower ( p  < 0.001) in the RM (2.3 ± 2.2 and 4.7 ± 3.7%) than in the NO-RM (5.2 ± 2.1 and 11.1 ± 5.2%), and PaO2 at PP30 and PPpost20 was higher ( p  < 0.001) in the RM (67.3 ± 4.2 and 60.1 ± 9.4 kPa) than in the NO-RM (50.2 ± 7.4 and 45.5 ± 11.1 kPa). Static compliance of the respiratory system at PP30 and PPpost20 was greater ( p  < 0.001) in the RM (2.4 ± 0.2 and 2.1 ± 0.4 mL cmH2 O −1 kg –1 ) than in the NO-RM (0.9 ± 0.4 and 1.2 ± 0.2 mL cmH2 O −1 kg –1 ). Conclusions and clinical relevance: In dogs undergoing laparoscopy, ARM followed by 5 cmH2 O PEEP improves gas exchange and respiratory system mechanics.